2023
DOI: 10.1038/s41598-023-32172-9
|View full text |Cite
|
Sign up to set email alerts
|

Access to germasiloxanes and alkynylgermanes mediated by earth-abundant species

Abstract: The reactions between silanols or terminal acetylenes with alkynylgermanes have been accomplished using potassium bis(trimethylsilyl)amide as the catalyst. This strategy has provided an entry point into various organogermanes including germasiloxanes and alkynylgermanes. Remarkably, not only KHMDS but also simple bases such as KOH can serve as efficient catalysts in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Highly-stable low-toxic organogermanium compounds have recently been used as reagents in the synthesis of complex organic molecules 2 , 3 . Stachowiak‑Dłużyńska et al reported an efficient protocol for the reactions between alkynylgermanes and silanols or terminal acetylenes using a commercially-available potassium bis(trimethylsilyl)amide (KHMDS) as the catalyst 4 . The KHMDS catalyst allowed a dealkynative coupling to synthesize a variety of organogermanes such as alkynylgermanes and germasiloxanes.…”
Section: Introductionmentioning
confidence: 99%
“…Highly-stable low-toxic organogermanium compounds have recently been used as reagents in the synthesis of complex organic molecules 2 , 3 . Stachowiak‑Dłużyńska et al reported an efficient protocol for the reactions between alkynylgermanes and silanols or terminal acetylenes using a commercially-available potassium bis(trimethylsilyl)amide (KHMDS) as the catalyst 4 . The KHMDS catalyst allowed a dealkynative coupling to synthesize a variety of organogermanes such as alkynylgermanes and germasiloxanes.…”
Section: Introductionmentioning
confidence: 99%
“…The application of Earth-abundant species as catalysts have gained recent significant attention in organic chemistry. 38–49 Considering our recent success in activating organometalloids under sustainable catalysis, 50–56 we reasoned that an appropriate catalytic manifold could provide an efficient platform to generate diversified libraries of protected propargyl alcohols. To address the limitations of previously mentioned methods, herein we report the KHMDS-catalyzed addition of silylacetylenes to ketones.…”
Section: Introductionmentioning
confidence: 99%
“…After that, a siloxane-exchange reaction between the metal-bounded symmetric disiloxane ( C ) and the excess trialkylsilanol generates an unsymmetric disiloxane-ligated cobalt complex ( D ). 13 It undergoes dissociation to liberate the anticipated unsymmetric disiloxanes and regenerates cobalt complex ( A ) and completes the catalytic cycle. 6 c Another possible reaction pathway for this catalytic formation of unsymmetric disiloxanes directly from two different silanols ( B to D ) also exists.…”
mentioning
confidence: 99%